a) Find the vertical asymptotes of the function `y = (x^2 + 1)/(3x - 2x^2)` b) Confirm your answer to part (a) by graphing the function.
The vertical asymptotes are the values which x can not equal. Therefore, `` `` 0
In order to find the zeroes solve: `3x-2x^2=0`
Factor to get: `x(3-2x)=0`
Use the zero property to solve for x. Set each factor equal to zero.
x = 0 and 3-2x=0
Therefore x=0, and x=`3/2`
Since x cannot equal these 2 values because it will make your denominator equal to 0 which would be undefined, the vertical asymptotes are: `x=0 and x=w3/2`